Racionalismo e Ilustración en la enseñanza del latín: evolución de las gramáticas escolapias en la segunda mitad del siglo XVIII - Espino Martín, Javier (Cuadernos de Filología Clásica. Estudios Latinos, 2003)
In this study, we try to show how rational methods are being introduced in Scolapian grammar handbooks during the eighteen century. The Society of Jesus supremacy imposed the formalist method of the Arte Regio by Juan Luis de la Cerda, and of the Sintaxis by Torrella. Although the first Scolapian grammars used to follow the Jesuit teaching pattern, however, even from the very beginning, some features of the national system are timidly introduced in Calasantian handbooks. Nevertheless, since the second half of the eighteen century, once the Jesuits were expelled, Scolapian grammar teaching, as well as national methods, were fully adopted